PENGEMBANGAN KONSEP KEADILAN DALAM FILSAFAT HUKUM: STUDI INTEGRASI NILAI-NILAI MORAL DAN ETIKA DALAM SISTEM HUKUM - Ilhamni, Feri (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
The problem in this study lies in the subjectivity of moral and ethical values that vary across cultures and societies, making it difficult to create universal standards in law. Modern legal systems dominated by the positivist paradigm tend to reject the integration of moral and ethical values that are considered subjective. This study uses a library research approach, which aims to explore and analyze the concept of justice in legal philosophy through the integration of moral and ethical values in the legal system. The main sources of data in this study are books, scientific journal articles, and research reports. The results of the study show that: 1). The concept of justice in legal philosophy developed through the integration of moral and ethical values is that the integration of moral and ethical values provides a new dimension to the concept of justice in legal philosophy, enriching the understanding of substantive and inclusive justice. 2). The integration of moral and ethical values in the legal system to improve the legitimacy and justice of the law in the eyes of society is that this integration makes the law more adaptive to the social and cultural context, increasing legitimacy and a sense of justice in society. 3). Challenges and Obstacles in Integrating Moral and Ethical Values into the Legal System are that the main challenges include the subjectivity of moral values, resistance from the positivist paradigm, and the risk of sacrificing legal certainty.